172 Late effects on rectum and urinary bladder in cervical cancer brachytherapy: dose effect relationship and ICRU rectum and bladder point dose correlation. (13th November 2020) - Mathews, S; Balachandran, H; Kumar, A; Joseph, J; Kumar, R; Krishna KM, J; James, FV
Abstract : Traditional Manchester Point based brachytherapy continues to be popularly practiced even when CT imaging has replaced traditional X-rays for treatment planning. ICRU bladder and rectal Point doses are documented and monitored as predictive of Organs at Risk (OAR) doses. Aim: To study the late effects of treatment and its correlation with dose volume parameters. Dosimetric correlation between volume doses and corresponding ICRU Rectum and Bladder point doses were studied. Materials and Methods: 101 Cervical cancer patients treated during 2014 – 2016 with radio-chemo therapy and CT based Brachytherapy treatment planning were eligible. Bladder, rectum and sigmoid were retrospectively contoured on CT data sets and Dose volume histogram for doses to the most exposed portion of (D2cc) OARs were recorded and compared with corresponding ICRU Point doses. Patients were followed up till August 2019 and toxicity data collected prospectively using CTCAE V4.03. Correlation of toxicity with doses received was attempted. Results: The overall incidence of bladder toxicity was 19.8% and rectal toxicity 30.7%. Grade 2 &3 toxicities were < 5% for bladder and 13% for rectum. 1 patient developed Grade 4 rectal toxicity. The threshold dose for bladder toxicity was D2cc- 89 Gy and 67 Gy for rectum. Grade 4 toxicity occurred with D 2cc - 83 Gy. There was no correlation between bladder D2cc and ICRU bladder point doses. Moderate correlation was seen between rectal D2cc and dose to point R (0.62) Conclusion: Monitoring D2cc of OARs should be attempted on CT in an attempt to reduce morbidity even with traditional planning.